Epilepsy Seizures without Triggers - Fatima Shad, Kaneez (IntechOpen, 2023)
According to the World Health Organization, nearly 80% of people with epilepsy live in low- and middle-income countries and could live seizure-free if properly diagnosed and treated. Among the structural and genetic triggers that may lead to epilepsy are head trauma, abnormal synaptic connectivity, receptor subunits anomalies, and atypical ionic channel function. Developing brains are specifically susceptible to seizures for many reasons, for example, the presence of enhanced excitation due to the early production of excitatory neurotransmitters, and the fact that the inhibitory neurotransmitter GABA causes excitation early in life. These studies help to clarify why the very young brain is exceptionally prone to seizures. The chapters presented in this book describe how structural, genetic, infectious, and metabolic abnormalities can lead to epileptogenesis. Nevertheless, many underlying disease mechanisms that can lead to epilepsy remain unknown.